Alexander Jeffrey McKelway papers - McKelway, Alexander Jeffrey, 1866-1918.
Correspondence, speeches, writings, articles, financial records, printed matter, scrapbook of obituary notices and condolence letters, and other papers relating primarily to child labor reform, particularly McKelway's role as secretary for the Southern States of the National Child Labor Committee. Other subjects include women's suffrage, prohibition, national political affairs, the Hoke Smith-Georgia Historical Association correspondence of 1917, and McKelway family matters. Family papers include boyhood letters of Benjamin Mosby McKelway and papers pertaining to the life of St. Clair McKelway. Correspondents include Carrie Chapman Catt, Josephus Daniels, Florence Kelley, Henry F. Keenan, Amos Pinchot, Gifford Pinchot, Theodore Roosevelt, Hoke Smith, Joseph P. Tumulty, Woodrow Wilson, the Georgia Historical Association, and Norman Hapgood, editor of Harper's Weekly.
Clergyman, reformer, and Southern secretary of the National Child Labor Committee.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index to the Theodore Roosevelt and Woodrow Wilson letters within the general correspondence as well as indexes to portions of the speech, article, and book file are available in the Library of Congress Manuscript Reading Room and at
Keywords: Catt, Carrie Chapman, -- 1859-1947 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Hapgood, Norman, -- 1868-1937 -- Correspondence; Keenan, Henry F. -- 1850- -- Correspondence; Kelley, Florence, -- 1859-1932 -- Correspondence; McKelway, Benjamin Mosby, -- 1895-1976 -- Correspondence; McKelway, St. Clair, -- 1845-1915.; Pinchot, Amos, -- 1873-1944 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Smith, Hoke, -- 1855-1931.; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; McKelway family; McKelway family -- Correspondence; Georgia Historical Association; National Child Labor Committee (U.S.); Harper's weekly; Child labor -- Southern States; Child labor -- United States; Prohibition -- United States; Women -- Suffrage -- United States; United States -- Politics and government -- 1865-1933.; United States -- Social conditions -- 1865-1918.; Clergy; Reformers